Analisis Kesiapan Petugas Pertolongan Kecelakaan Penerbangan Dan Pemadam Kebakaran (PKP-PK) Dalam Kecelakaan Pesawat Di Bandar Udara Tunggul Wulung Cilacap - Brian Indra Laksono; Suprapti Suprapti (Jurnal of Management and Social Sciences, 2024)
This research aims to find out: This research aims to find out: analyze the readiness of PKP-PK unit officers in efforts to improve aviation safety by National and International Regulations. This is because, when an accident occurs in the waterside area, the PKP-PK unit must be ready and alert to handle the condition. The PKP-PK unit's lack of alertness can pose a danger to the aircraft if an aircraft is about to land. In carrying out their duties, PKP-PK personnel have their respective roles according to the personnel's abilities and licenses. The license held by a personnel is of course a benchmark for the performance of the personnel in carrying out their duties, so that the performance of each PKP-PK unit is not completely the same or equivalent.This study used qualitative research methods. The data collection techniques used were observation, interviews, documents, and documentation along with observations. The researcher directly carried out observations, the researcher also explained the results of the data taken during interviews and observations. For the researcher's interview with the resource persons, namely PKP-PK officers consisting of the Head Unit, Supervisor, Senior PKP-PK, and Junior PKP-PK at mogul Wulung Airport, Cilacap, and also in the form of implementation documents for the data analysis techniques used, namely data collection, data reduction, data presentation, discussion, and conclusions. The readiness of PKP-PK officers at mogul Wulung Cilacap Airport is a key factor in handling plane accidents effectively. Factors such as knowledge, skills, equipment, training, and external factors such as weather can influence officer readiness. To increase readiness, there needs to be ongoing efforts to improve training, maintain equipment, and conduct simulations regularly. Good readiness of PKP-PK officers will help minimize risks in emergencies and protect the lives of passengers and aircraft crew. Handling aircraft accidents by PKP-PK officers at Nggul Wulung Airport, Cilacap is a very important task to ensure the safety of passengers and aircraft crew. The obstacles faced by PKP-PK officers can hamper the effectiveness of the actions of PKP-PK officers at Nggul Wulung Airport, Cilacap. Therefore, it is necessary to implement several solutions to increase the effectiveness of handling aircraft accidents and minimize the associated risks. These solutions must be implemented with caution and take into account the specific situation in each location and country. Improved training, coordination, investment in equipment, resource planning, and risk evaluation are key steps in overcoming these obstacles and improving the ability of PKP-PK officers at mogul Wulung Airport, Cilacap in responding to aircraft accidents quickly and effectivel